Immigration, Working Conditions, and Compensating Differentials - Chad Sparber; Madeline Zavodny (Institute of Labor Economics (IZA), 2020)
The large inflow of less-educated immigrants that the United States has received in recent decades can worsen or improve U.S. natives' labor market opportunities. Although there is a general consensus that low-skilled immigrants tend to hold "worse" jobs than U.S. natives, the impact of immigration on U.S. natives' working conditions has received little attention. This study examines how immigration affected U.S. natives' occupational exposure to workplace hazards and the return to such exposure over 1990 to 2018. The results indicate that immigration causes less-educated U.S. natives' exposure to workplace hazards to fall, and instrumental variables results show a larger impact among women than among men. The compensating differential paid for hazard exposure appears to fall as well, but not after accounting for immigration-induced changes in the returns to occupational skills.
Keywords: J81; J31; F22; 330; immigration; hazardous jobs; compensating differentials; risk premium